Improving Junior High School Students' Response and Science Learning Outcomes in Special Sports Class Through Animated Learning Media - Elbadiansyah; Masyni; Achmad Maulana (Postgraduate, University of Mataram, 2024)
This research aims to improve student responsiveness and science learning outcomes in special sports classes by using animated learning media. Through this research, it is hoped that student responses during teaching and learning activities will increase and science learning activities will become enjoyable so that ultimately, they can improve science learning outcomes. This research is a three-cycle Classroom Action Research. Each cycle consists of four stages. The research subjects were 36 class VIII students (special sports class) at one of the state junior high schools in Samarinda. The research instruments used were student responsiveness observation sheets during teaching and learning activities, learning activity observation sheets, and learning outcomes instruments (post-test questions). The resulting data is then analyzed for the average value. In the first cycle learning outcomes reached 42% and student responsiveness to teacher activities in teaching and learning was only 56% (less). In cycle 2 learning outcomes reached 72% and student responsiveness to teacher activities in teaching and learning increased to 68%. In cycle 3 the science learning results for the special sports class finally reached classical completeness of 88% and responsiveness to teacher activities in teaching and learning reached 93% (exceeding the classical completeness standard). The results of this research show that animated learning media can improve responsiveness and science learning outcomes in special sports classes.